2023
DOI: 10.3390/biomedicines11030748
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Dysbiosis and Neurological Conditions Often Manifesting with Chronic Pain

Abstract: The prevalence of neurological conditions which manifest with chronic pain is increasing globally, where the World Health Organisation has now classified chronic pain as a risk factor for death by suicide. While many chronic pain conditions have a definitive underlying aetiology, non-somatic conditions represent difficult-to-diagnose and difficult-to-treat public health issues. The interaction of the immune system and nervous system has become an important area in understanding the occurrence of neuroinflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 86 publications
(181 reference statements)
0
25
0
Order By: Relevance
“…The 16S rRNA gene sequencing and phylum analysis revealed an increased relative abundance of Verrucomicrobia and drastic change in the ratio of Bacteroidetes and Firmicutes ( Shen et al, 2017 ). Accumulating evidence suggested that the imbalance of Bacteroidetes and Firmicutes ratio contributed to the development of chronic pain ( Garvey, 2023 ). In another study, elevated abundance of Verrucomicrobia was linked to chronic abdominal pain ( Kang et al, 2019 ).…”
Section: Molecular Mechanisms Underlying the Development Of Cipnmentioning
confidence: 99%
“…The 16S rRNA gene sequencing and phylum analysis revealed an increased relative abundance of Verrucomicrobia and drastic change in the ratio of Bacteroidetes and Firmicutes ( Shen et al, 2017 ). Accumulating evidence suggested that the imbalance of Bacteroidetes and Firmicutes ratio contributed to the development of chronic pain ( Garvey, 2023 ). In another study, elevated abundance of Verrucomicrobia was linked to chronic abdominal pain ( Kang et al, 2019 ).…”
Section: Molecular Mechanisms Underlying the Development Of Cipnmentioning
confidence: 99%
“…Both human and rodent studies indicated that probiotics reduce chronic-psychological-stress-induced abnormal brain activity and related cognitive dysfunctions by lowering plasma CORT and adrenocorticotropic hormone levels, restoring hippocampal 5-HT and NE levels, and normalizing immunity with low plasma levels of TNF-α but high levels of IL-10, an anti-inflammatory cytokine [ 171 , 172 , 173 ]. Several probiotics, as psychobiotics, for example, Bifidobacterium and Lactobacillus , deliver mental health benefits with neurobehavioral effects, which have been used in humans for improving cognitive function and for preventing and treating patients with behavioral impairment in neurodegenerative diseases, such as Alzheimer’s disease and Parkinson’s disease, and in diseases with neuropsychiatric disorders, such as anxiety, depression, and impulsively and compulsively disrupted social behavior [ 75 , 77 , 78 , 79 , 83 , 84 ]. Based on findings, targeting the gut microbiota has been recognized as a novel therapeutic option for patients with neuropsychiatric disorders [ 63 , 73 , 74 ].…”
Section: Cecal Microbiota Transplantation Social Stress and Injurious...mentioning
confidence: 99%
“…Targeting the intestinal microbiota with the goal of restoring its balance has been recognized as a novel therapeutic option for patients with neuropsychiatric disorders [ 72 , 73 , 74 ]. Several probiotics, as psychobiotics, such as Bifidobacterium and Lactobacillus , which can benefit mental health, have been used for preventing and treating patients with behavioral impairment, such as anxiety, depression, and impulsively and compulsively disrupted social behavior, via regulating the MGB, MGI, or both axes [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. However, the use of purified probiotics benefits has shown mixed results, with several weaknesses including transient beneficial effects, requiring continuous administration over time due to the host’s resident microbial populations and “colonization resistance” [ 85 ].…”
Section: Introductionmentioning
confidence: 99%
“…The association between the gastrointestinal microbiota, IBD, chronic inflammation, and CRC has become an area of much investigation. Alteration in the resident microbial species of the large intestine appears to greatly impact diseases of the gastrointestinal tract (GIT) [14]. This review aims to outline the relationship between GIT dysbiosis, inflammation, and the development of CRC, where insights into novel treatment approaches are also described.…”
Section: Introductionmentioning
confidence: 99%